PERAN ORGANISASI BADAN PERMUSYAWARATAN DESA DALAM PEMBANGUNAN PEMERINTAHAN DESA : (Studi Desa Margoajaya Kabupaten Mesuji Timur Kabupaten Mesuji) - Nita Ajeng Liyani; Tuti Handayani (Jurnal Progress Administrasi Publik (JPAP), 2022)
The Village Consultative Body (BPD) is a village organization formed based on the potential of the village and efforts to facilitate activities or development in the village. For inequitable development in the village, the government involves community participation to raise awareness that basically village development uses the principles carried out by the community and for the community. This public awareness will lead to a high sense of belonging and responsibility. Many BPDs in areas are not running, therefore this study aims to determine the role of the Village Consultative Body (BPD) in the Margoajaya village government, Mesuji Timur District, Mesuji Regency. And to find out what factors hinder the role of the Village Consultative Body (BPD) against the village government in Margojaya Village, Mesuji Timur District, Mesuji Regency. This research was conducted with a descriptive qualitative method. And concluded that the role of the Village Consultative Body (BPD) towards the Margoajaya village government, Mesuji Timur District, Mesuji Regency was optimal the supporting aspects were the surrounding community and the obstacles were time and passive participation during deliberation.   Keywords: BPD, Role, Society